Asus / Muhammad Luqman Zulkifli - Zulkifli, Muhammad Luqman (2022)
This assignment is about identifying the problem with the product. The company that I have chosen is AsusTeK Computer Inc. by Taiwanese multitional computer and phone hardware and electronics company. From their variety of products, I have chosen the Asus ROG Chariot Core Gaming Chair to do my analysis. In this case study, I have done the SWOT analysis to identify the strength, weaknesses, opportunities, and threats of the Asus ROG Chariot Core Gaming Chair. The main problem I identified on this Asus ROG Chariot Core Gaming Chair is that the chair is extremely expensive. From the problem, I can come up with the best solution which is make a big discount to attract more people to buy the product like other Asus product with the discount.